2011
DOI: 10.1088/0957-0233/23/1/015104
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity improvement of a fibre Bragg grating pH sensor with elastomeric coating

Abstract: A new optical pH sensor based on fibre Bragg grating (FBG) is demonstrated. The sensor consists of a FBG coated with pH sensitive hydrogel. The sensing was performed through the detection of wavelength shifts resulting from the induced strain on the FBG due to mechanical expansion of the hydrogel. An elastomeric coating was applied before the hydrogel coating to improve the sensitivity. The sensor performance was investigated by simulating the hydrogel swelling and the strain induced on the FBG. The swelling o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…However, the fabrication complexity of the sensor, as well as its slightly reduced pH operational range make this FO-SPR configuration less attractive. In contrast, other studies demonstrated lower sensitivity values ranging from nm/pH to nm/pH, only when operating in a narrow pH range [ 33 , 34 ]. It can be thus observed that the PANI/Pt-coated reflection-type FO-SPR sensor prepared and characterized in this work, provides a decent sensitivity value higher than nm/pH on a broad range of pH values (1 to 14).…”
Section: Resultsmentioning
confidence: 96%
“…However, the fabrication complexity of the sensor, as well as its slightly reduced pH operational range make this FO-SPR configuration less attractive. In contrast, other studies demonstrated lower sensitivity values ranging from nm/pH to nm/pH, only when operating in a narrow pH range [ 33 , 34 ]. It can be thus observed that the PANI/Pt-coated reflection-type FO-SPR sensor prepared and characterized in this work, provides a decent sensitivity value higher than nm/pH on a broad range of pH values (1 to 14).…”
Section: Resultsmentioning
confidence: 96%
“…5 It is obvious that ε F ∕δ will increase with the increase of b, i.e., the thickness of the coating in this research, which will result in a larger Bragg wavelength shift; that is to say, a high sensitivity of the sensor can be achieved by using as thick a coating as possible.…”
Section: Structure Of the Sensormentioning
confidence: 84%
“…This feature makes LPGs useful elements for chemical and biotechnological applications. 28 A hydrogel-coated LPG sensor was proposed and demonstrated by Corres 34 refractive index and reflection-based intensity-modulated fiber-optic sensors were demonstrated; [35][36][37] and recently, a photonic crystal fiber coated with hydrogel was demonstrated by Hu et al 38 In this article, the authors propose a hydrogel-coated FBG-based pH sensor. Modified FBG sensors by using etched or side polished fiber to increase the evanescent field interaction with the surrounding media are being used for chemical sensing.…”
Section: Introductionmentioning
confidence: 94%
“…Long period gratings (LPGs) have a distinct advantage in this context, as they allow coupling of light between core and cladding modes. [26][27][28][29][30][31] The estimation of pH is an obvious factor in environmental monitoring such as waste water monitoring, seawater analysis, food processing industry, river and industry water quality monitoring, blood analysis, and in various chemical and biomedical fields. [8][9][10][11][12][13][14] However, LPG sensing suffers from some disadvantages such as incapability for multipoint sensing, broad transmission resonance, and appearance of multiple peaks, which lowers the accuracy due to the presence of leaky modes.…”
Section: Introductionmentioning
confidence: 99%